Art 1954 A Comparative Analysis Of The Maliki And Hanbali Schools On Schistosomiasis Prevention As An Application of Sadd Al-Dhara'iʿ:: Evidence From The Watumaeta Village Community of Indonesia - Hanifa Az-Zahra; Mayyadah; Ahmad arief; Nurinayah (Al Mashaadir : Jurnal Ilmu Syariah, 2026)
Schistosomiasis remains a persistent public health problem in Central Sulawesi, particularly in the Napu Valley, where transmission dynamics are strongly influenced by environmental sanitation and community behavior. Amid the dominance of biomedical and public health approaches, the integration of Islamic legal principles as a normative framework for disease prevention remains limited. Addressing this gap, this study aims to identify and critically examine community-based schistosomiasis prevention practices, analyze their normative legitimacy through the concept of sadd zari’ah, and articulate the theoretical contribution of Islamic law in strengthening socially grounded disease prevention through a comparative analysis of the Maliki and Hanbali schools. This study employs a qualitative approach with an empirical legal research design, utilizing observation, semi-structured interviews, and documentation, which are analyzed descriptively. The findings indicate that preventive practices include sanitation improvement, prohibition of open defecation, control of snail habitats, use of personal protective equipment, mass drug administration, and strengthened health education as systematic efforts to interrupt transmission pathways. From a comparative perspective, the Maliki school advocates a stricter application of sadd zari’ah by closing all potential avenues leading to disease transmission, whereas the Hanbali school allows a degree of flexibility provided that precautionary principles and risk prevention are maintained. Both schools substantively agree that such preventive measures constitute the protection of life (hifz al-nafs) and should be upheld as an obligation to avert harm. Therefore, schistosomiasis prevention practices in Watumaeta Village are not only effective from a public health standpoint but also represent a contextualized application of Islamic legal principles, reinforcing the relevance of sadd zari’ah as a normative foundation for community-based disease prevention in endemic settings   Keywords: Schistosomiasis prevention, Sadd zari’ah, Islamic law, Mazhab comparison